الوحدة البنائية في القرآن الكريم - قرين، فضيلة (Kuliyyah of Islamic Revealed Knowledge and Human Science, International Islamic University Malaysia, 1998)
This study explores the internal structure of the Qur'an and analyses the essential methodological elements of the structural unity of the Qur'an, and determines their impact on the Quranic sciences. Consequently, this study analyzes the critical relationship among the Qur'an,the arabic language, and I'jaz (the miraculous dimension of the Qur'an). It traces the history of the Quranic unity in the works of Tafsir and Quranic sciences and relates the science of concordance (al-tanasub) to the Quranic system. By so doing the research has succeeded in his demonstration of the organic unity in the Quran and concluded that the Qur'an does not belong to any positivistic linguistic style and that its meanings should not be completely tied to the occasions of revelation, so that it accommodates and gives space to new cases and projections. The study finally argues that I'jaz, in spite of its importance should not be regarded as the exclusive miraculous dimension of the Qur'an, Rather it should be comprehensively treated and approached in a way to establish the unity of the Quran. I'jaz understood in this particular manner wtll open wider horizons for the miraculous dimension of the Qur'an both in form and content.